Imaging in phenytoin induced neurotoxicity: a case series - Arora, Manali; Kumar Boruah, Deb; Thakker, Vishal; Bhanwra, Sangeeta (International Journal of Research in Medical Sciences, 2017)
Phenytoin is a commonly used anti-epileptic drug for various types of seizure disorders except for absent seizures. Long term dose dependant neurological side effects of phenytoin therapy include cerebellar atrophy, cerebral atrophy and brain stem atrophy. Skull hyperostosis, gum hypertrophy and megaloblastic anemia are other known effects of Long term therapy. We present four cases depicting clinical and neuroimaging findings of Phenytoin induced Toxicity.